Arabisasi Kata-kata Asing Sebagai Usaha Mempertahankan Gramatika dan Morfologi Bahasa Arab - Anida Yuspa (Institut Agama Islam Negeri Metro, 2018)
Interaction between nations in the world causes inter-language struggles that can cause positive or negative effects on one another. So there is a language that is very dominating other languages, and some eventually die without any speakers, or are forced to adopt some of the words or grammar of other languages. There are three groups of expert opinions on the arabization of foreign words: the conservative, the pragmatic, and the moderate. The opinions of moderate groups are more representative of all the aspirations of Arabic experts.